Métodos de formação de grupos na aprendizagem colaborativa, baseados em características dos participantes - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The formation of collaborative groups at the University is a relevant topic for the field of science and mathematics education and teaching. Formal education has undergone several adaptations due to the Covid-19 Pandemic framework, where face-to-face classes have migrated to online remote teaching. For this, the teacher needs to look for resources and new tools to work in groups. This research arose from my concern since graduation in relation to the formation of groups, so, facing a new stage of the Master’s Degree, we left for an investigation that has Quali-quantitative characteristics that aimed to investigate which methods of group formation are best for the case study in question. The methods used to achieve the objectives were online activities with heterogeneous groups, an online questionnaire applied to the 15 students of the Calculus-1 course at UFAM participating in this research, to investigate their satisfaction with the formation of groups and the use of computational tools. The results obtained by this research describe that heterogeneous groups were formed efficiently from a previous assessment, where their components could collaborate with each other, sharing their knowledge through activities carried out in groups formed in the class of Calculo-1 at the Federal University of amazonas in the year 2020.
Keywords: Software - Desenvolvimento; Software educacional; Tecnologia educacional; CIENCIAS HUMANAS: EDUCACAO: ENSINO-APRENDIZAGEM; Grupos heterogêneos; Aprendizagem significativa; Software computacional